Is Galatians Just A “Guy Thing”?: A Theological Reflection - Gaventa, Beverly Roberts (Interpretation, 2000)
Is there “good news” for women in Galatians? The letter points to God's new creation, which liberates both women and men from their worlds of achievement and identity. The most important thing to be said about us is that we are “in Christ.”